(untitled) (Archives of Mechanics - Test, 2014)
The subject of the present paper is the applicability of hydrophobic surfaces for passive anti-icing protection. The experiments were focused on freezing droplets and on various droplet impingement and deformation scenarios. Droplet impact was investigated using high-speed camera for surfaces with different physico-chemical properties. To investigate the difference in droplet behavior on the surfaces with different wettability the steel and the aluminum plates were used and compared with specially designed surfaces characterized by a low surface energy. The influence of air humidity on droplet freezing was confirmed. The effective prevention of icing was observed only if humidity was removed from the system during the experiment.